The Concept of Maqasid al-Syari'ah in the Interpretation of Legal Verses: A Comparative Study of Tafsir al-Qurthubi and Tafsir al-Misbah - Wardah, Muhammad; Situmorang, Jubair (Manunggal Halim Jaya, 2025)
This study discusses the maqāṣid al-syarī'ah approach in interpreting the verses of the Qur'an with a focus on two monumental tafsir books, namely Tafsir al-Qurṭubī and Tafsir al-Miṣbāḥ by M. Quraish Shihab. The background of this study is based on the need to understand how the exegetes apply the principles of maqāṣid al-syarī'ah in contextualizing legal verses. With a content analysis approach, the qualitative research method uses a comparative study of the two tafsirs. The results show that Tafsir al-Qurṭubī tends to emphasize the normative-classical approach with a focus on legal derivation (istinbāṭ al-aḥkām) according to the fiqh tradition. At the same time, Tafsir al-Miṣbāḥ prioritizes a contextual approach and benefit value. This methodological difference indicates a dialectic between the classical exegetical heritage and the needs of contemporary society. This research contributes to developing maqāṣid-based exegesis that integrates tradition and contemporary reality.